Reservoir stimulation of marine natural gas hydrate-a review. (15th January 2023) - Wang, Xiaochu; Sun, Youhong; Li, Bing; Zhang, Guobiao; Guo, Wei; Li, Shengli; Jiang, Shuhui; Peng, Saiyu; Chen, Hangkai
Abstract: Low production rate, limited recovery range, and short period of stabilized production of natural gas hydrate (NGH) field trials indicate a large gap to commercial production. To improve the efficiency of gas recovery from NGH reservoir, a large number of studies on reservoir stimulation have been reported. In this review, various aspects of reservoir fracability, including brittleness, fracture toughness, and fracability index model are comprehensively analyzed to provide an overall view on the generation of fractures in marine NGH reservoir. The main reservoir stimulation methods are summarized into four aspects: hydraulic fracturing, jet breaking, overlying layer modification and split grouting, of which the working principle, advantages, and limitations are highlighted. It indicates split grouting is the most promising method for achieving two goals of both reservoir skeleton reinforcement and permeability enhancement. Besides, the production enhancement by reservoir stimulation of non-diagenetic hydrate reservoir should be further evaluated considering the evolution of artificial seepage channels during hydrate decomposition. Finally, further developments are suggested to obtain reliable results of the fracability of NGH reservoir, bridge the gap of reservoir stimulation between concept design and practical application, and highlight the combination between reservoir stimulation and NGH reservoir stability for safe and efficient gas production. Highlights: Basic theories of NGH reservoir fracability are briefly reviewed. Reservoir stimulation methods for marine hydrate reservoir are summarized into four groups. Simulations on enhancement of production by reservoir stimulation are presented.